Agrobiodiversity Index scores show agrobiodiversity is underutilized in national food systems - Jones, Sarah K.; Estrada-Carmona, Natalia; Juventia, Stella D.; Dulloo, Mohammad Ehsan; Laporte, Marie-Angélique; Villani, Chiara; Remans, Roseline (Springer, 2021)
The diversity of plants, animals and microorganisms that directly or indirectly support food and agriculture is critical to achiev ing healthy diets and agroecosystems. Here we present the Agrobiodiversity Index (based on 22 indicators), which provides a monitoring framework and informs food systems policy. Agrobiodiversity Index calculations for 80 countries reveal a moderate mean agrobiodiversity status score (56.0 out of 100), a moderate mean agrobiodiversity action score (47.8 out of 100) and a low mean agrobiodiversity commitment score (21.4 out of 100), indicating that much stronger commitments and concrete actions are needed to enhance agrobiodiversity across the food system. Mean agrobiodiversity status scores in consumption and conservation are 14–82% higher in developed countries than in developing countries, while scores in production are consis tently low across least developed, developing and developed countries. We also found an absence of globally consistent data for several important components of agrobiodiversity, including varietal, functional and underutilized species diversity.